Some identities on degenerate trigonometric functions - Kim, Taekyun; Kim, Dae San (Karpats'kì matematinì publìkacìï, 2025)
In this paper, we study several degenerate trigonometric functions, which are degenerate versions of the ordinary trigonometric functions, and derive some identities among such functions by using elementary methods. Especially, we obtain multiple-angle formulas for the degenerate cotangent and degenerate sine functions. У цій статті ми вивчаємо кілька вироджених тригонометричних функцій, які є виродженими версіями звичайних тригонометричних функцій, та виводимо деякі тотожності для таких функцій за допомогою елементарних методів. Зокрема, ми отримуємо формули кратних кутів для виродженого котангенса та виродженого синуса.